Neurological and MRI Findings in Malformations of Cortical Development and The Value of 3D FLAIR MRI: A Single-Center Study - Şükriye Yılmaz; Aslı Ercili Erdal; Mehmet Can Pençe; Berna Ucan; Deniz Yüksel; Ayşe Kaçar Bayram (OSMANGAZİ JOURNAL OF MEDICINE, 2026)
Malformations of cortical development (MCDs) are heterogeneous neurodevelopmental disorders resulting from abnormalities in neuronal proliferation, migration, and post-migrational organization, and they represent an important cause of pediatric epilepsy. High-resolution magnetic resonance imaging (MRI), particularly three-dimensional fluid-attenuated inversion recovery (3D-FLAIR), improves the detection of subtle cortical abnormalities such as focal cortical dysplasia (FCD).This study aimed to describe the distribution, clinical characteristics, and epilepsy-related features of malformations of cortical development in children, and to evaluate the added value of 3D FLAIR MRI in the detection and characterization of focal cortical dysplasia. A total of 47 pediatric patients were included. Post-migrational abnormalities were the most common findings (74.4%), followed by migration disorders (21.2%) and abnormalities of proliferation or apoptosis (4.2%). Seizures were the most frequent presenting symptom, and FCD was the most common subtype. Among the 17 patients with FCD, four lesions not visible on routine imaging were detected using the 3D-FLAIR sequence. In conclusion, MCDs are an important cause of pediatric epilepsy. High-resolution MRI, particularly 3D FLAIR imaging, improves the detection of subtle cortical abnormalities, especially focal cortical dysplasia. Optimized MRI protocols using widely available 1.5-T systems may significantly enhance diagnostic accuracy and support therapeutic planning.